Idiopathic myositis ossificans of the lateral pterygoid muscle in the paediatric patient: A case report - Pritesh Narsinh; Yuxin Ken Lin (Elsevier, 2021)
Myositis ossificans traumatica rarely affects the muscles of mastication. Since 1924, there has only been one case reported to affect the muscles of mastication in the paediatric population. The purpose of this paper is to present an 11-year-old girl with calcification of her right lateral pterygoid muscle with no evidence of previous trauma to the muscle. The clinical history and radiographic features resembled an extremely rare form of myositis ossificans also known as myositis ossificans idiopathica.